Inclusive Leadership and Psychological Safety among Employees in the Automotive Manufacturing Industry - Rizky Purnomo Adji Churnawan; Natalia Guadelupe Freitas (International Journal of Psychology and Health Science, 2026)
Human resources constitute a critical element in sustaining organizational success, particularly in automotive manufacturing environments that require precision, efficiency, and strict safety compliance. This study explored the association between inclusive leadership and psychological safety among employees of an automotive manufacturing company in Cikarang, Bekasi, Indonesia. Using a quantitative, cross-sectional correlational design, data were collected from 100 employees recruited through convenience sampling. The study employed two standardized instruments: the Inclusive Leadership Scale by Carmeli et al. (2010) and the Psychological Safety Scale developed by O'Donovan et al. (2020) and later refined by Sasaki et al. (2022). Statistical analyses, performed with SPSS, included descriptive statistics, reliability assessment, assumption testing, Pearson correlation, and simple linear regression. The findings indicated a positive and significant link between inclusive leadership and psychological safety (r = 0.46, p < 0.001) and confirmed that inclusive leadership significantly predicts psychological safety (β = 0.46, p < 0.001), explaining 21 percent of its variance (R² = 0.21). These results highlight that leaders who are open, approachable, and supportive of participation substantially contribute to a psychologically safe and collaborative workplace climate. Practically, inclusive leadership emerges as a strategic approach for strengthening employee engagement, encouraging innovation, and sustaining performance in the automotive manufacturing industry.